PENERAPAN FRAMEWORK LARAVEL PADA PEMBANGUNAN APLIKASI KEMAJUAN BELAJAR SISWA BERBASIS WEB DENGAN MENGGUNAKAN METODE WATERFALL - Ilham Pradana; Nyimas Sopiah (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
Technological advances in various sectors have made data processing digitalized so that information can be accessed quickly. SD Negeri Simpang Sari has implemented computer technology but data management in its application, teachers still use a manual system with paper so that it is considered ineffective and can increase errors when inputting data, as well as taking report cards which are still done offline, so this study aims to develop applications The learning progress of the Simpang Sari Elementary School students is web-based using the waterfall method. The design system in making applications for student learning progress uses the PHP programming language and the Laravel framework and MySQL in database management. The development of the application for student learning progress at SD Negeri Simpang Sari aims to provide academic information faster with effective and integrated data management and storage so that it will make it easier for parents and students to access the website to see progress in grades and lesson schedules anywhere with adequate internet network quality.